Francis Bacon - Russell, John (London : Thames and Hudson London, 1979)
Based on conversations with the artist which extended over several years, John Russell's study reveals much about Bacon the man and Bacon the artist in a way that has not been attempted before. Bacon's intentions and his achievements, both frequently misunderstood in the past, are here corrected and set in perspective, and the record of his major paintings is brought up to date in the text and in the many illustrations for this new edition.
Engels
boek
Keywords: Bacon, Francis